Cultural Distance and its Effect on Cross-Border Entry Mode: Latin American Evidence (2013)
This paper studies if "cultural distance" between two firms determines the entry mode of a foreign organization. We study two different modes of entering a market: cooperative agreements and acquisitions. We analyze a database that gathers 1,292 cooperative ventures and acquisitions in ten Latin American countries from 1998 to 2004. Evidence is consistent with firms selecting cooperative agreements over acquisitions the larger the cultural distance, particularly when we proxy cultural distance in two dimensions: individualism-collectivism and masculinity-femininity. Results hold when we run a logistic regression controlling for other variables among them, the Heritage Foundation Indexes, and a same-language dummy.